Omvårdnad av den geriatriska hunden - Freij, Malin (2014)
Due to progresses constantly being made in veterinary medicine combined with increasing knowledge in pet owners, the dogs of today gets older than before. The population of geriatric dogs is there for constantly growing, which makes them an important group of patients on small animal clinics and hospitals.